Automated Vertebrae Extraction Using Watershed Segmentation and Tree-based Modelling Approach (Journal of Fiber Bioengineering and Informatics, 2015)
Vertebra segmentation and extraction are essential steps for automated vertebrae fracture assessmentsystem. This study focuses on vertebra segmentation, which is a challenging task due to high noise andpoor contrast of X-Ray images. The objective of this study is to develop and test an automated cervicalvertebrae extraction to facilitate the medical researchers and physicians. The novelty of the proposedmethod is the combination of watershed segmentation and tree-based modelling algorithm. The proposedmethod has been successfully applied to a set of 50 cervical X-Ray images. Five performance metricsare calculated, which are accuracy, sensitivity, specificity, correlation and error where the best obtainedresults are 0.9886, 0.0655, 0.99, 0.7246 and 0.01135, respectively.